Новые виды растениеобитающих клещей (Acariformes, Tarsonemidae) Крыма и Кавказа - Шаронов, А.А. (Вестник зоологии, 1983)
Three monocotyledon plant-dwelling mite species of the genera Sfeneotarsonemus Beer, 1954 and Tarsonemus Can. et Fanz, 1876 from the Crimea and the Caucasus are described as new: S. vasiljevae sp. n.— similar to S. varicosus Liv, Mitr. et Shar, differs by the absence of sejugal apodeme and apodemes IV, and by the shape of the lobus and prosternum; S. livschitzi sp. n.— similar to S. casteli Liv, Mitr. et Shar, differs by coal chetze I position, shape of lobus and apodemes 11, and by the length of crucial chetae; 7. sevastianovi sp. n.— similar to S. lacustris Shar., differs by lobus and metasternum shape, position of inner humeral chetae and solenidium Taa on tibiotarsus.